Fundamentals of communications and networking - Solomon, Michael (Michael G.) 1963-; Kim, David (Jones & Bartlett Learning, 2013)
Fundamentals of Communications and Networking helps readers understand today's networks and the way they support the evolving requirements of different types of organizations. It covers the critical issues of designing a network that will meet an organization's performance needs and discusses how businesses use networks to solve business problems. Using examples and exercises, this book incorporates hands-on activities to prepare readers to proficiently understand and design modern networks and their requirements